Assessment of Left Main Coronary Artery Luminal Diameter Using Quantitative Coronary Analysis and Optical Coherence Tomography - Mehmedbegović, Zlatko; Jelic, Dario; Mladenovic, Djordje; Travica, Lazar; Simic, Damjan; Dukic, Djordje; Sarenac, David; Ristic, Marko; Zejak, Nikola; Bojovic, Dijana; Stankovic, Goran (Medical Research, 2026)
Introduction: Accurate assessment of left main (LM) coronary lumen dimensions is essential during percutaneous coronary intervention (PCI). Quantitative coronary analysis (QCA) is routinely used, yet its agreement with high-resolution intravascular imaging modalities such as optical coherence tomography (OCT) in the LM segment remains incompletely defined. Methods: Thirty patients who underwent LM PCI were evaluated using follow-up angiography and OCT. Eight matched lumen parameters were assessed using 2D QCA, 3D QCA, and OCT. Differences between modalities were analyzed using repeated-measures ANOVA for normally distributed variables and Friedman’s test for minimal lumen area (MLA). Linear correlations were assessed descriptively, and agreement was evaluated using Bland–Altman analysis. Results: Significant modality-dependent differences were observed across most lumen parameters. QCA demonstrated strong linear associations with OCT for reference- and mean-based lumen metrics, whereas correlations were weaker for extreme (minimal and maximal) dimensions. Bland–Altman analysis revealed minor mean differences between QCA and OCT but wide limits of agreement, indicating substantial inter-individual variability despite consistency at the group level. Conclusion: QCA provides reasonably consistent estimates of reference and mean lumen dimensions in the LM segment but shows limited association with OCT for extreme measurements. Despite strong linear associations, individual variability remains considerable, supporting OCT as the preferred modality for precise lumen assessment, stent sizing, and procedural optimization in LM PCI.